Effect of Replacing Maize with Malted Barley Grain on Egg Quality and Laying Hens Performance of White Leghorn (Global Journal of Science Frontier Research, 2015)
The effect of various levels of malted barley grain (MBG) on the laying performance and egg quality of white leghorn pullets was investigated. A total of 180 white leghorn pullets were randomly assigned to four dietary treatments consisting of 0%, 10%, 20% and 30% barley as a replacement for maize. There were 45 birds per treatment and three replicates of 15 birds and the experiment was laid in a completely randomized design. The evaluated traits were egg production, egg weight, egg mass, feed consumption, feed conversion ratio, shell thickness, yolk weight, shell weight, yolk index, yolk diameter, yolk height, albumen height, yolk color and Haugh unit. The result showed significant increase in feed consumption, yolk color, albumen weight and shell thickness (P
Keywords: egg quality; laying hens; malted barley grain; performance